2010
DOI: 10.1111/j.1600-0404.2009.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Valproate in children with newly diagnosed idiopathic generalized epilepsy

Abstract: Objectives-Sparse information on dose-response characteristics for initial antiepileptic drug monotherapy in children with idiopathic generalized epilepsy (IGE) is available. The aim of this study is to characterize the therapeutic dose of valproate in children with newly diagnosed IGE.Materials and methods-Effect of initial valproate monotherapy and doses associated with seizure freedom were examined in consecutive children with IGE identified from a New Onset Seizure Clinic.Results-Of 84 patients identified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Twenty-six percent of the cohort was in the high seizure probability group, which is consistent with previously reported rates of seizure intractability. [1][2][3] In contrast, three-quarters of the population exhibited a low probability of seizure recurrence over 2 years. This latter group's initial higher probability of seizures soon after diagnosis was likely attributable to the time required to titrate and optimize AED therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six percent of the cohort was in the high seizure probability group, which is consistent with previously reported rates of seizure intractability. [1][2][3] In contrast, three-quarters of the population exhibited a low probability of seizure recurrence over 2 years. This latter group's initial higher probability of seizures soon after diagnosis was likely attributable to the time required to titrate and optimize AED therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of multiple new efficacious antiepileptic drugs (AEDs), 20% to 35% of children with newly diagnosed epilepsy continue to have seizures. [1][2][3] Several biologically based factors have been examined to understand this disease course, including underlying brain disorders and structural abnormalities, seizure type/etiology, and genetics. 4,5 However, these biological factors, which are nonmodifiable, do not fully explain the variability in seizure outcomes.…”
mentioning
confidence: 99%
“…Another study evaluated valproate monotherapy in 84 children with new-onset IGE and reported seizure freedom in 57% with an additional 10 patients who achieved seizure freedom but had to discontinue valproate because of intolerable adverse events [59]. Table 4.…”
Section: Class IV Trialsmentioning
confidence: 98%
“…Antiepileptic drugs (AEDs) are the primary treatment modality for most patients with epilepsy, and the overall goal of treatment is no seizures, no side effects and best quality of life (Glauser, 2002). Although multiple efficacious AEDs are available to treat children with epilepsy, one-third of children with newly diagnosed epilepsy continue to have seizures despite the use of an AED (Geerts et al, 2010;Holland & Glauser, 2007;Holland, Monahan, Morita, Vartzelis, & Glauser, 2010;Kwan & Brodie, 2000). The precise reason for experiencing continued seizures despite the use of medications is often unknown, but may be because of seizure type, disease etiology, genetics, medication selection/combination, underlying brain abnormalities, or AED nonadherence (Berg, Testa, & Levy, 2011;Geerts et al, 2012;Glauser et al, 2006;Modi, Ingerski, Rausch, & Glauser, 2011;.…”
mentioning
confidence: 99%